Super-sharp ceramic tile cutting blade
By adding specific components and process processing to the diamond saw blades, an efficient cutting piece is formed, which solves the problems of insufficient sharpness and edge collapse in the cutting of existing diamond saw blades in ceramic tile, and achieves higher cutting accuracy and wear resistance .
Patent Information
- Application Number
- CN202411584473.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-07
AI Technical Summary
The existing diamond saw blades are not sharp enough during the tile cutting process, which is prone to damage, and the cutting accuracy and quality cannot be guaranteed, making them prone to edge collapse.
Using cutting sheets including diamond particles, metal carbonyl compounds, copper-covered carbonyl compounds and binding agents, the iron pentacarbonyl compounds are reacted under high pressure environment, and deposited on the cutting part through CVD technology. Pores are formed during the sintering process by combining paraffin to improve the Particle binding degree.
It significantly improves the sharpness and wear resistance of the cutting sheet, reduces the wear rate, improves the accuracy and quality of tiles cutting, and effectively avoids edge collapse.
Smart Images

Figure SMS_10 
Figure SMS_11
Abstract
Description
Technical Field
[0001] The invention relates to the field of cutting blades, in particular to an ultra-sharp tile cutting blade. Background Art
[0002] Diamond saw blades are the most consumed diamond tools in the world. They are widely used in the processing of stone, glass, ceramics, cast iron materials, as well as in the construction of houses, roads, bridges and other projects. With the continuous improvement of diamond saw blade manufacturing technology and the continuous reduction of production costs, its application field is still expanding, especially in the direction of tile cutting, and the demand is also constantly expanding.
[0003] The high hardness and excellent physical and mechanical properties of diamond make diamond cutting blades an indispensable material for processing various hard materials. Diamond tools are made by mixing metal powder and artificial diamond particles, pressing and sintering. When the matrix uses a mixture of single-element powders, there are the following disadvantages: high sintering temperature, insufficient alloying of elements, and incomplete densification after sintering. Due to the insufficient sharpness of the diamond blade, the blade is easily damaged during high-speed cutting, and the cutting accuracy and cutting quality cannot be guaranteed, and edge collapse is prone to occur.
[0004] Therefore, it is necessary to provide a new super-sharp tile cutting disc to solve the above-mentioned technical problems. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides an ultra-sharp tile cutting blade.
[0006] The ultra-sharp tile cutting blade provided by the present invention comprises a substrate and a cutting portion located at the edge of the substrate, and is characterized in that the cutting portion comprises the following components by weight: 65-80 parts of diamond particles, 10-25 parts of metal carbonyl compounds, 35-55 parts of binders, and 30-40 parts of copper-coated carbon with a particle size of 0.5-0.6 mm.
[0007] Furthermore, the metal carbonyl compound is produced by reacting ultrafine iron powder with carbon monoxide under high pressure to generate an iron pentacarbonyl compound.
[0008] Furthermore, the binder includes copper powder, tin powder and paraffin wax.
[0009] Furthermore, the substrate is a metal copper substrate.
[0010] Furthermore, the particle size distribution of the diamond particles is 60-80 mesh.
[0011] Furthermore, the method for preparing the tile cutting blade comprises the following steps:
[0012] S1. Accurately weigh each material;
[0013] S2, substrate processing, processing the metal copper substrate into a desired shape and size, and performing surface treatment;
[0014] S3, mixing, mixing diamond particles, copper powder, tin powder, and copper-coated carbon;
[0015] S4, pressing, putting paraffin wax and the mixed diamond particles, copper powder, tin powder, and copper-coated carbon into a mold for pressing to obtain a cutting part blank;
[0016] S5, sintering, placing the pressed cutting part blank into a sintering furnace for sintering, heat preservation and cooling;
[0017] S6, preparation of metal carbonyl compounds, reacting ultrafine iron powder with carbon monoxide under high pressure to generate iron pentacarbonyl compounds;
[0018] S7, depositing, depositing the generated iron pentacarbonyl compound on the cutting part blank by CVD technology to obtain a finished cutting part;
[0019] S8, welding, using a suitable welding rod or welding wire to weld the finished cut portion to the metal copper matrix;
[0020] S9, thinning, thinning the finished product;
[0021] S10. Inspection: Check whether the finished product has any defects in appearance.
[0022] Furthermore, in the step S5, the sintering temperature is 800-1000° C., the holding time is set to 1-2 hours, and after the holding time is over, natural cooling or forced cooling to room temperature is adopted.
[0023] Furthermore, during the preparation of the metal carbonyl compound, the pressure is maintained at 80-100 bar, the temperature is maintained at 800-1200° C., and the maintenance time is 6-12 hours.
[0024] Furthermore, in the step S7, the deposition temperature is 500-600° C., and the deposition time is 1-3 h.
[0025] Compared with the related art, the ultra-sharp tile cutting blade provided by the present invention has the following beneficial effects:
[0026] 1. The present invention applies copper-coated carbon compounds with a particle size of 0.5-0.6 mm, which can be better dispersed in the mixture to form a more uniform distribution and higher cutting efficiency. The use of smaller and uniform particle sizes helps to reduce the segregation of materials during the pressing process and avoid local performance differences. Among them, copper-coated carbon compounds with a particle size of 0.5 mm have the best effect and effectively improve the edge collapse of tiles.
[0027] 2. During the sintering process of the binder of the present invention, the paraffin wax will gradually burn out, releasing gases (mainly carbon dioxide and water vapor) to form pores. The pores provide diffusion channels, allowing atoms or molecules between particles to migrate more easily, promoting the bonding between particles. As the sintering temperature increases, the pores begin to gradually close, the contact area between the particles increases, and the particles begin to rearrange. The presence of pores can serve as stress release points to reduce stress concentration caused by volume changes in the material during the sintering process. The wear rate of the cutting part is smaller, which effectively improves the wear resistance and hardness.
[0028] 3. The present invention applies iron pentacarbonyl compound, which acts as a catalyst to make the bond stronger, effectively improve the hardness, control the thickness difference below 0.05 mm, and significantly improve the sharpness.
[0029] 4. In the present invention, paraffin wax and mixed diamond particles, copper powder, tin powder and copper-coated carbon are placed in a mold for pressing. As the subsequent sintering temperature increases, the paraffin wax will gradually burn out and the pores will gradually close, which is beneficial to the subsequent demolding process. DETAILED DESCRIPTION
[0030] The present invention will be further described below in conjunction with the embodiments.
[0031] Embodiment 1
[0032] In a specific implementation process, an ultra-sharp tile cutting blade includes a metal copper substrate and a cutting portion located at the edge of the metal copper substrate, and the cutting portion includes the following components by weight: 65 parts of diamond particles, 10 parts of metal carbonyl compounds, 60 parts of copper powder, 8 parts of tin powder, 1 part of paraffin wax, and 30 parts of copper-coated carbon with a particle size of 0.5 mm;
[0033] Metal carbonyl compounds are produced by reacting ultrafine iron powder with carbon monoxide under high pressure to generate iron pentacarbonyl compounds: .
[0034] The particle size distribution of diamond particles is 60 mesh.
[0035] Embodiment 2
[0036] In a specific implementation process, an ultra-sharp tile cutting blade includes a metal copper substrate and a cutting portion located at the edge of the metal copper substrate, and the cutting portion includes the following components by weight: 70 parts of diamond particles, 15 parts of metal carbonyl compounds, 65 parts of copper powder, 10 parts of tin powder, 2 parts of paraffin wax, and 35 parts of copper-coated carbon with a particle size of 0.55 mm;
[0037] Metal carbonyl compounds are produced by reacting ultrafine iron powder with carbon monoxide under high pressure to generate iron pentacarbonyl compounds: .
[0038] The particle size distribution of diamond particles is 70 mesh.
[0039] Embodiment 3
[0040] In a specific implementation process, an ultra-sharp tile cutting blade includes a metal copper substrate and a cutting portion located at the edge of the metal copper substrate, and the cutting portion includes the following components by weight: 80 parts of diamond particles, 25 parts of metal carbonyl compounds, 70 parts of copper powder, 12 parts of tin powder, 3 parts of paraffin wax, and 40 parts of copper-coated carbon with a particle size of 0.6 mm;
[0041] Metal carbonyl compounds are produced by reacting ultrafine iron powder with carbon monoxide under high pressure to generate iron pentacarbonyl compounds: .
[0042] The particle size distribution of diamond particles is 80 mesh.
[0043] Embodiment 4
[0044] In the specific implementation process, the preparation method of the ultra-sharp tile cutting blade includes the following steps:
[0045] S1. Accurately weigh the materials in Example 1;
[0046] S2, substrate processing, processing the metal copper substrate into a desired shape and size, and performing surface treatment;
[0047] S3, mixing, mixing diamond particles, copper powder, tin powder, and copper-coated carbon;
[0048] S4, pressing, putting paraffin wax and the mixed diamond particles, copper powder, tin powder, and copper-coated carbon into a mold for pressing, applying a pressure of 100 MPa for pressing, the pressing time is 5 minutes, and obtaining a cutting part blank;
[0049] S5, sintering, placing the pressed cutting part blank into a sintering furnace for sintering, heat preservation and cooling, wherein the sintering temperature is 800°C, the heat preservation time is set to 1h, and after the heat preservation time is over, natural cooling or forced cooling is adopted to room temperature;
[0050] S6. Preparation of metal carbonyl compounds: ultrafine iron powder is reacted with carbon monoxide under high pressure, the pressure is maintained at 80 bar, the temperature is maintained at 800°C, and the maintenance time is 6 hours to generate iron pentacarbonyl compounds: ;
[0051] S7, deposition, the generated iron pentacarbonyl compound is deposited on the cutting part blank by CVD technology, the deposition temperature is 500°C, the deposition time is 1h, and the iron pentacarbonyl compound decomposes at high temperature to generate metallic iron particles and carbon monoxide: , the metallic iron particles are deposited on the cutting part blank to obtain the finished cutting part;
[0052] S8, welding, using a suitable welding rod or welding wire to weld the finished cutting part and the metal copper substrate together. Before welding, the copper substrate and the cutting part need to be surface cleaned and activated;
[0053] S9, thinning, thinning the finished product to control the thickness difference within 0.05mm;
[0054] S10. Inspection: Check whether the finished product has any defects on its appearance, such as cracks, pores, etc.
[0055] It should be noted that the preparation steps of copper-clad carbon are as follows:
[0056] 1. Select graphene material with a particle size of 0.6 mm;
[0057] 2. Clean the surface of the carbon material, remove impurities and perform surface activation treatment;
[0058] 3. Heat the copper target to an evaporating state, use CVD equipment to deposit copper atoms on the surface of the carbon material under the protection of an inert gas (such as argon), introduce carbon monoxide (CO) as a reducing agent to form a copper layer.
[0059] The following steps are used for the screening of carbon materials:
[0060] 1. Select the graphene material that needs to be screened;
[0061] 2. Select the appropriate sieve specifications. For carbon materials with a particle size of 0.6 mm, select a sieve with a diameter of 0.6 mm and use multiple layers of sieves for graded screening;
[0062] 3. Set the screen to an appropriate vibration frequency and amplitude;
[0063] 4. Sprinkle the graphene material evenly on the sieve, and collect the carbon material with a particle size of 0.6 mm after the vibration ends.
[0064] Embodiment 5
[0065] In the specific implementation process, the preparation method of the ultra-sharp tile cutting blade includes the following steps:
[0066] S1. Accurately weigh the materials of Example 2;
[0067] S2, substrate processing, processing the metal copper substrate into a desired shape and size, and performing surface treatment;
[0068] S3, mixing, mixing diamond particles, copper powder, tin powder, and copper-coated carbon;
[0069] S4, pressing, putting paraffin wax and the mixed diamond particles, copper powder, tin powder, and copper-coated carbon into a mold for pressing, applying a pressure of 200 MPa for pressing, the pressing time is 6 minutes, and obtaining a cutting part blank;
[0070] S5, sintering, placing the pressed cutting part blank into a sintering furnace for sintering, heat preservation and cooling, wherein the sintering temperature is 900°C, the heat preservation time is set to 1.5h, and after the heat preservation time is over, it is cooled naturally or forcedly to room temperature;
[0071] S6. Preparation of metal carbonyl compounds: ultrafine iron powder is reacted with carbon monoxide under high pressure, the pressure is maintained at 90 bar, the temperature is maintained at 1000°C, and the time is maintained for 8 hours to generate iron pentacarbonyl compounds: ;
[0072] S7, deposition, the generated iron pentacarbonyl compound is deposited on the cutting part blank by CVD technology, the deposition temperature is 550°C, the deposition time is 2h, and the iron pentacarbonyl compound decomposes at high temperature to generate metallic iron particles and carbon monoxide: , the metallic iron particles are deposited on the cutting part blank to obtain the finished cutting part;
[0073] S8, welding, using a suitable welding rod or welding wire to weld the finished cutting part and the metal copper substrate together. Before welding, the copper substrate and the cutting part need to be surface cleaned and activated;
[0074] S9, thinning, thinning the finished product to control the thickness difference within 0.04mm;
[0075] S10. Inspection: Check whether the finished product has any defects on its appearance, such as cracks, pores, etc.
[0076] It should be noted that the preparation steps of copper-clad carbon are as follows:
[0077] 1. Select graphene material with a particle size of 0.55 mm;
[0078] 2. Clean the surface of the carbon material, remove impurities and perform surface activation treatment;
[0079] 3. Heat the copper target to an evaporating state, use CVD equipment to deposit copper atoms on the surface of the carbon material under the protection of an inert gas (such as argon), introduce carbon monoxide (CO) as a reducing agent to form a copper layer.
[0080] The following steps are used for the screening of carbon materials:
[0081] 1. Select the graphene material that needs to be screened;
[0082] 2. Select the appropriate sieve specifications. For carbon materials with a particle size of 0.55 mm, select a sieve with a diameter of 0.55 mm and use multiple layers of sieves for graded screening;
[0083] 3. Set the screen to an appropriate vibration frequency and amplitude;
[0084] 4. Sprinkle the graphene material evenly on the sieve, and collect the carbon material with a particle size of 0.55 mm after the vibration ends.
[0085] Embodiment 6
[0086] In the specific implementation process, the preparation method of the ultra-sharp tile cutting blade includes the following steps:
[0087] S1. Accurately weigh the materials of Example 3;
[0088] S2, substrate processing, processing the metal copper substrate into a desired shape and size, and performing surface treatment;
[0089] S3, mixing, mixing diamond particles, copper powder, tin powder, and copper-coated carbon;
[0090] S4, pressing, putting paraffin wax and the mixed diamond particles, copper powder, tin powder, and copper-coated carbon into a mold for pressing, applying a pressure of 300 MPa for pressing, and the pressing time is 8 minutes to obtain a cutting part blank;
[0091] S5, sintering, putting the pressed cutting part blank into a sintering furnace for sintering, heat preservation and cooling, wherein the sintering temperature is 1000°C, the heat preservation time is set to 2h, and after the heat preservation time is over, it is cooled naturally or forced to room temperature. During the sintering process, the paraffin will gradually burn away, releasing gas (mainly carbon dioxide and water vapor) to form pores. The pores provide diffusion channels, making it easier for atoms or molecules between particles to migrate and promoting the combination between particles. As the sintering temperature increases, the pores begin to gradually close, the contact area between particles increases, and the particles begin to rearrange;
[0092] S6. Preparation of metal carbonyl compounds: ultrafine iron powder is reacted with carbon monoxide under high pressure, the pressure is maintained at 100 bar, the temperature is maintained at 1200°C, and the time is maintained for 12 hours to generate iron pentacarbonyl compounds: ;
[0093] S7, deposition, the generated iron pentacarbonyl compound is deposited on the cutting part blank by CVD technology, the deposition temperature is 600°C, the deposition time is 3h, and the iron pentacarbonyl compound decomposes at high temperature to generate metallic iron particles and carbon monoxide: , the metallic iron particles are deposited on the cutting part blank to obtain the finished cutting part;
[0094] S8, welding, using a suitable welding rod or welding wire to weld the finished cutting part and the metal copper substrate together. Before welding, the copper substrate and the cutting part need to be surface cleaned and activated;
[0095] S9, thinning, thinning the finished product to control the thickness difference within 0.03mm;
[0096] S10. Inspection: Check whether the finished product has any defects on its appearance, such as cracks, pores, etc.
[0097] It should be noted that the preparation steps of copper-clad carbon are as follows:
[0098] 1. Select graphene material with a particle size of 0.5 mm;
[0099] 2. Clean the surface of the carbon material, remove impurities and perform surface activation treatment;
[0100] 3. Heat the copper target to an evaporating state, use CVD equipment to deposit copper atoms on the surface of the carbon material under the protection of an inert gas (such as argon), introduce carbon monoxide (CO) as a reducing agent to form a copper layer.
[0101] The following steps are used for the screening of carbon materials:
[0102] 1. Select the graphene material that needs to be screened;
[0103] 2. Select the appropriate sieve specifications. For carbon materials with a particle size of 0.5 mm, select a sieve with a diameter of 0.5 mm and use multiple layers of sieves for graded screening;
[0104] 3. Set the screen to an appropriate vibration frequency and amplitude;
[0105] 4. Sprinkle the graphene material evenly on the sieve, and collect the carbon material with a particle size of 0.5 mm after the vibration ends.
[0106] Comparative Example 1
[0107] In the specific implementation process, the tile cutting disc includes the following components by weight: 60 parts of copper matrix, 65 parts of diamond particles, 60 parts of copper powder, and 8 parts of tin powder. The diamond particles, tin powder and copper powder are mixed evenly, and the mixed powder is fixed on the copper matrix by pressing and sintering.
[0108] Comparative Example 2
[0109] In the specific implementation process, the tile cutting disc includes the following components by weight: 60 parts of copper matrix, 65 parts of diamond particles, 5 parts of cobalt powder, 60 parts of copper powder, 5 parts of silver powder, and 8 parts of tin powder. The diamond particles, tin powder, tin powder, cobalt powder, silver powder and copper powder are evenly mixed, and the mixed powder is fixed on the copper matrix by pressing and sintering.
[0110] Comparative Example 3
[0111] In the specific implementation process, the tile cutting disc includes the following components by weight: 60 parts of copper matrix, 65 parts of diamond particles, 5 parts of cobalt powder, 60 parts of copper powder, 5 parts of iron powder, and 8 parts of manganese powder. The diamond particles, tin powder, manganese powder, cobalt powder, iron powder and copper powder are evenly mixed, and the mixed powder is fixed on the copper matrix by pressing and sintering.
[0112] Comparative Example 4
[0113] In the specific implementation process, the tile cutting disc includes the following components by weight: 60 parts of copper matrix, 65 parts of diamond particles, 5 parts of carbon fiber, 60 parts of copper powder, 5 parts of iron powder, and 8 parts of manganese powder. The diamond particles, tin powder, manganese powder, carbon fiber, iron powder and copper powder are evenly mixed, and the mixed powder is fixed on the copper matrix by pressing and sintering.
[0114] Experiment 1
[0115] In the experiment, the raw materials of Example 1, Example 2, and Example 3 were used and prepared by the preparation methods of Example 4, Example 5, and Example 6, and the tile cutting discs prepared by Comparative Example 1 and Comparative Example 2 were respectively subjected to hardness test, wear test, and cutting test. The specific test average data are as follows:
[0116]
[0117] As shown in the above table, the data of comparative examples 1 and 2 after applying copper-coated carbon compounds, iron pentacarbonyl compounds and paraffin wax respectively are quite different from those of Example 1, Example 2 and Example 3. In Example 1, Example 2 and Example 3, the cutting speed and hardness are effectively improved. During the sintering process, the paraffin wax will gradually burn out, releasing gases (mainly carbon dioxide and water vapor) to form pores. The pores provide diffusion channels, so that atoms or molecules between particles can migrate more easily, promoting the bonding between particles. As the sintering temperature increases, the pores begin to gradually close, the contact area between the particles increases, and the particles begin to rearrange. The presence of pores can be used as stress release points to reduce the stress concentration caused by volume changes in the material during the sintering process. In terms of wear rate, the wear rate of the cutting part is small and the wear resistance is better. The composite structure of copper-coated carbon gives it higher strength and hardness, and it is tougher than pure carbon fiber materials.
[0118] Experiment 2
[0119] The raw materials of Example 1, Example 2 and Example 3 were respectively used and the preparation methods of Example 4, Example 5 and Example 6 were used to prepare the tile cutting discs prepared by Comparative Example 1 and Comparative Example 2, and the edge collapse, service life and sharpness tests were performed respectively, wherein the edge collapse conditions were divided into four standards: no edge collapse, slight, general and severe. The specific test average data are as follows:
[0120]
[0121] As shown in the above table, the data of Comparative Example 1 and Comparative Example 2 after applying copper-coated carbon compound, iron pentacarbonyl compound and paraffin respectively are quite different from those of Example 1, Example 2 and Example 3. After adding copper-coated carbon and paraffin treatment, the chipping effect of the tile edge is effectively improved. The use of smaller and more uniform particle size helps to reduce the segregation of the material during the pressing process and avoid local performance differences, which effectively improves the chipping effect of the tile edge. At the same time, the thickness difference is controlled below 0.05 mm, and the sharpness is also significantly improved.
[0122] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. For those skilled in the art, it is obvious that the present invention is not limited to the details of the above exemplary embodiments, and the present invention can be implemented in other specific forms without departing from the spirit or basic features of the present invention. Therefore, no matter from which point of view, the embodiments should be regarded as exemplary and non-restrictive. The scope of the present invention is limited by the attached claims rather than the above description. Therefore, it is intended to include all changes within the meaning and scope of the equivalent elements of the claims in the present invention, and any mark in the claims should not be regarded as limiting the claims involved.
[0123] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. An ultra-sharp tile cutting blade, comprising a base and a cutting portion located at the edge of the base, characterized in that: The cutting part comprises the following components by weight: 65-80 parts of diamond particles, 10-25 parts of metal carbonyl compounds, 35-55 parts of binders, and 30-40 parts of copper-coated carbon; The particle size of the copper-coated carbon is 0.5-0.6 mm.
2. The ultra-sharp tile cutting blade according to claim 1, characterized in that: The metal carbonyl compound is an iron pentacarbonyl compound.
3. The ultra-sharp tile cutting blade according to claim 2, characterized in that: The binder includes one or more of copper powder, tin powder and paraffin.
4. The ultra-sharp tile cutting blade according to claim 3, characterized in that: The substrate is a metal copper substrate.
5. The ultra-sharp tile cutting blade according to claim 4, characterized in that: The particle size distribution of the diamond particles is 60-80 meshes.
6. The ultra-sharp tile cutting blade according to claim 5, characterized in that: The preparation method of the tile cutting disc comprises the following steps: S1. Accurately weigh each material; S2, substrate processing, processing the metal copper substrate into a desired shape and size, and performing surface treatment; S3, mixing, mixing diamond particles, copper powder, tin powder, and copper-coated carbon; S4, pressing, putting paraffin wax and the mixed diamond particles, copper powder, tin powder, and copper-coated carbon into a mold for pressing to obtain a cutting part blank; S5, sintering, placing the pressed cutting part blank into a sintering furnace for sintering, heat preservation and cooling; S6, preparation of metal carbonyl compounds, reacting ultrafine iron powder with carbon monoxide under high pressure to generate iron pentacarbonyl compounds; S7, depositing, depositing the generated iron pentacarbonyl compound on the cutting part blank by CVD technology to obtain a finished cutting part; S8, welding, using a suitable welding rod or welding wire to weld the finished cut portion to the metal copper matrix; S9, thinning, thinning the finished product; S10. Inspection: Check whether the finished product has any defects in appearance.
7. The ultra-sharp tile cutting blade according to claim 6, characterized in that: In the step S5, the sintering temperature is 800-1000° C., the holding time is set to 1-2 hours, and after the holding time is over, natural cooling or forced cooling to room temperature is adopted.
8. The ultra-sharp tile cutting blade according to claim 6, characterized in that: During the preparation of the metal carbonyl compound, the pressure is maintained at 80-100 bar, the temperature is maintained at 800-1200° C., and the maintenance time is 6-12 hours.
9. The ultra-sharp tile cutting blade according to claim 6, characterized in that: In the step S7, the deposition temperature is 500-600° C. and the deposition time is 1-3 hours.
Citation Information
Patent Citations
Diamond saw blade and machining process thereof
CN102079109A
High-strength diamond cutting disk and preparing method thereof
CN105458244A
Preparation method of alloy electrical contact material
CN105861864A
High-precision ultrathin diamond cutting disk and preparation method therefor
CN105921739A
Diamond grinding wheel bar and preparation method thereof
CN106956224A